Penyusunan Laporan Keuangan Berdasarkan SAK EMKM di Masa Epidemi pada UMKM - Sugiyanto, Sugiyanto; Kartolo, Rachmat; Marjohan, Masno (Journal Pemberdayaan Masyarakat Indonesia, 2023)
The important for MSMEs in Indonesia for business sustainability through financial reporting in accordance with Law No. 20 of 2008 concerning Micro, Small and medium enterprises due to a lack of understanding in the Implementation of financial reporting based on SAK EMKM. Especially to partners during the epidemic in MSMEs in Cianjur, West Java, they really need it. Partner problems faced by MSMEs in Cianjur, West Java Province are as follows: First (1) MSMEs are still recording manually, have not kept books based on EMKM Financial Accounting Standards properly, still traditionally (2) Have not kept books in accordance with SAK EMKM Financial Accounting Standards . Solution to Problems First stage: Community service activities include preparation of training materials. Second stage: is the implementation stage, starting with identifying the level of knowledge and basic accounting by conducting questions and answers between trainers and participants plan-do-check-act. The third stage: Socialization of basic accounting and the practice of preparing financial statements based on SAK EMKM. The results achieved in this community service activity were MSME actors in Cianjur, West Java, business people were able to compile financial reports based on good SAK EMKM.